APPLICATION OF THE PROJECT-BASED APPROACH IN STRATEGIC MANAGEMENT OF BUSINESS DEVELOPMENT IN THE REGION - KRYVOKULSKA, Natalia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article reveals the scientific vision of the ways of using the project approach in the strategic management of business development in the region. Goal of the article is to substantiate the importance of using the project approach in the strategic management of business development in the region. Research methods: to substantiate the importance of using the project approach in the strategic management of business development in the region, the systemic and structural approaches, the method of analysis and synthesis, the statistical method, and the generalization of conceptual provisions on the studied issues presented in the publications of scientists were used. From the standpoint of the targeted approach, the theoretical provisions on the use of the project approach in the strategic management of business development in the region are substantiated, which complement the existing ones by taking into account modern features (the need to support business during the war and stimulate its development in the post-war reconstruction, etc.) The author states the importance of ensuring: sustainable development of regions; greater publicity in the activities of all participants in territorial development (state bodies, local self-government bodies, business entities, etc.); conditions for the diffusion of innovations (new types of products and services, organizational experience and knowledge, etc.), which, accordingly, requires the use of a project approach in the strategic management of business development in the region. It is argued that the issues of using the strategic and project approaches in regional management and business management are correlated with each other, and the essence of strategic management of business development in the region is revealed through the implementation of a set of development strategies that should be interrelated and involve the use of the project approach. The author identifies the conditions that need to be taken into account in the course of implementation of projects on territory development management, in particular: publicity of regional projects, which means participation of scientists, entrepreneurs, the public, and experts in their preparation, implementation, monitoring and control; projects form the basis for economic, social and environmental reforms in the region, attracting investments for this purpose and implementing an innovative model of sustainable development management with the participation of various stakeholders, including business, etc. It is emphasized that the regional (local) business development program should be functionally aimed at: identifying promising vectors for the development of such business from the standpoint of its value for the territory; forming a dynamic and flexible model of expedient business activity in the dynamic environment of the region and supporting such activity, however, today the communication component of local economic support programs and the establishment of effective business communications need to be strengthened. It is noted that the formation and implementation of a business organization’s own development strategy is an important part of its management system, which, in turn, involves determining a systemic set of tactical tasks that need to be performed, and by their essential characteristics are projects that should be managed. In the context of future prospects, it is emphasized that the project team, especially its manager, should develop long-term relationships with the client, identify new business opportunities in such relationships and strategically use them.